GENERAL OVERVIEW OF THE COLLECTION OF PERSIAN MANUSCRIPTS OF THE NATIONAL LIBRARY OF THE REPUBLIC OF KAZAKHSTAN - Kambarbekova, Ғ.Ә.; Kari, Қ.А. (Journal of Oriental Studies, 2024)
In the article, it was examined a comprehensive overview of manuscripts in the Persian language, stored in the manuscript fund of the National Library of the Republic of Kazakhstan. A brief history of the distribution of Persian manuscripts in Kazakhstan and the needs of the local population for literature distributed in the form of Persian manuscripts were presented with specific examples. The main reason for this is that the Persian language was not only the language of poetry but also the language of science, especially historical works. These words are evidenced by the fact that since the Middle Ages Persian manuscripts written on various topics were widely distributed in the countries of Central Asia and were used as textbooks in local madrasas. Also, in favor of these words, the thematic and content features of manuscripts in the Persian language, stored in the manuscript fund of the National Library of the Republic of Kazakhstan, testify. It is also possible to say that literary, historical, philosophical, Sufi, dictionaries, manuscripts of fiqh, and various stories, and stories in the Persian language were taught in madrasahs of Central Asia and Kazakhstan even before the formation of the Soviet Union. As evidence of this, the grammar of the Arabic language, written in the Persian language, and the collection of poems by Hafiz ben Bidil, preserved in several versions in the manuscript fund of the National Library of the Republic of Kazakhstan, are considered comprehensively. The article mainly deals with the content and scientific significance of Persian manuscripts stored in the rare collection of the National Library of the Republic of Kazakhstan. During the research, Persian manuscripts were divided into three groups. The unique features of the manuscripts of each group and the problems that arise during the research have not been ignored. As much as possible, the article includes the chronology of Persian manuscripts and customers, seal, handwriting, scribes, place (city), and year of copying of these manuscripts. Keywords: Persian manuscript, classification, madrasah, textbook, literature, history, Muslim education.